The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1073/pnas.0500986102
|View full text |Cite
|
Sign up to set email alerts
|

Two essential but distinct functions of the mammalian abasic endonuclease

Abstract: The mammalian abasic endonuclease, APE1, has two distinct roles in the repair of oxidative DNA damage and in gene regulation. Here we show that both functions are essential for cell survival. Deletion of the APE1 gene causes embryonic lethality in mice, and no nullizygous embryo fibroblasts have been isolated. We have now established nullizygous embryo fibroblast lines from APE1 ؊/؊ mouse embryos that are transgenic with the ''floxed'' human APE1 (hAPE1) gene. Removal of hAPE1 by Cre expression through nuclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
222
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 204 publications
(230 citation statements)
references
References 36 publications
4
222
1
2
Order By: Relevance
“…Transgenic expression of Cre in these cells leading to deletion of the APE1 transgene triggered apoptosis. This observation and an independent study provide unequivocal evidence that APE1 is essential even for somatic cells [120,121]. Kelley and his colleagues had earlier shown that APE1 downregulation triggers apoptosis in several human cell lines [122].…”
Section: Ape1 Is Essential In Mammalian Cellsmentioning
confidence: 59%
“…Transgenic expression of Cre in these cells leading to deletion of the APE1 transgene triggered apoptosis. This observation and an independent study provide unequivocal evidence that APE1 is essential even for somatic cells [120,121]. Kelley and his colleagues had earlier shown that APE1 downregulation triggers apoptosis in several human cell lines [122].…”
Section: Ape1 Is Essential In Mammalian Cellsmentioning
confidence: 59%
“…The recent demonstration that siRNA may be used to down-regulate APE1 does however show promise for future studies to define the role of APE1 in mammalian cells in vivo [38]. However, complete depletion may be impossible as it is shown to be essential for cellular survival [39]. Although AP-site specific 5'endonucleolytic activity is the major function of APE1, there are a number of minor functions associated with APE1 as well, including 3'phosphodiesterase, 3'phosphoglycolase, 3'phosphatase and 3'-5'exonuclease capabilities.…”
Section: Mono-functional and Bi-functional Dna Glycosylases And Ap-simentioning
confidence: 99%
“…Apurinic/apyrimidinic endonuclease 1/redox factor‐1 (APE1/Ref‐1; henceforth referred to as APE1) is a multifunctional protein that is involved in repairing DNA damage via its endonuclease activity in base excision repair (Fung and Demple, 2005; Izumi et al ., 2005; Jiang et al ., 2009; Kelley et al ., 2014), and using its redox protein–protein signaling function to control the activity of numerous transcription factors such as STAT3, NFκB, AP‐1, p53, and hypoxia‐inducible factor 1α (HIF1α), among others (Cardoso et al ., 2012; Fishel et al ., 2015; Gaiddon et al ., 1999; Jiang et al ., 2010; Kelley et al ., 2012; Lando et al ., 2000; Logsdon et al ., 2016). It also contributes to the removal of damaged bases within RNA (Poletto et al ., 2016; Vascotto et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, it is not possible to generate stable APE1‐knockout cell lines (Tell et al ., 2009). Approaches to circumvent this dilemma have utilized conditional knockouts and siRNA knockdowns (Fung and Demple, 2005; Izumi et al ., 2005; Jiang et al ., 2010). For example, using siRNA knockdowns, our laboratory has previously identified APE1 directly regulating STAT3 transcriptional activity (Cardoso et al ., 2012), suppressing Nrf2‐induced gene expression (Fishel et al ., 2015) and, most recently, regulating carbonic anhydrase 9 (CA9) via HIF‐1α under hypoxic conditions (Logsdon et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%